School Bonding in Early Adolescence: Psychometrics of the Brief Survey of School Bonding - Whiteside-Mansell, Leanne; Weber, Judith L.; Moore, Page C.; Johnson, Danya; Williams, Ed R.; Ward, Wendy L.; Robbins, James M.; Phillips, B. Allyson (The Journal of early adolescence, 2015)
The comprehensive assessment of middle school student bonding is important for basic research and to evaluate interventions. In this study, the psychometric properties of three assessment tools found in the literature were examined individually and then combined to create a shorter survey. With minor modifications, the tools were found to be psychometrically sound; however, they were burdensome in length and contained redundancy. This motivated the development of a shorter tool that was included in a cyclical process of multiple samples of students (n = 53, 1,911, 2,050) in three phases. The cyclical process involved combining the three surveys, eliminating redundancy, and then examining the psychometric properties of the reduced survey. A final forth phase of the study resulted in a brief but comprehensive survey, Brief Survey of School Bonding. It was found to be psychometrically sound and appropriate for use with children 10 to 15 years of age.